Resistive pressure sensors based on freestanding membranes of gold nanoparticles. Issue 1 (8th December 2015) - Schlicke, Hendrik; Rebber, Matthias; Kunze, Svenja; Vossmeyer, Tobias
Abstract : A novel type of resistive pressure sensor, employing the electromechanical properties of a freestanding membrane of cross-linked gold nanoparticles, is presented in this communication. Abstract : In this communication the application of gold nanoparticle membranes as ambient pressure sensors with electromechanical signal transduction is demonstrated. The devices were fabricated by sealing microstructured cavities with membranes of 1, 6-hexanedithiol cross-linked gold nanoparticles, which were electrically contacted by metal electrodes deposited on both sides of the cavities. Variations of the external pressure resulted in a deflection of the membranes and, thus, increased the average interparticle distances. Therefore, the pressure change could easily be detected by simply monitoring the resistance of the membranes.